LAND SUITABILITY MODELING FOR FISHERY RESOURCE ENHANCEMENT IN THE PADANG PARIAMAN REGENCY, WEST SUMATERA, INDONESIA: GIS AND MULTI-CRITERIA EVALUATION APPROACHES - Gemilang, Wisnu Arya; Wisha, Ulung Jantama; Rahmawan, Guntur Adhi; Ondara, Koko; Dhiauddin, Ruzana (Indonesian Aquaculture Journal, 2024)
[Land Suitability Modeling for Fishery Resource Enhancement in the Padang Pariaman Regency, West Sumatera, Indonesia: GIS and Multi-Criteria Evaluation Approaches] Land suitability analysis is required for successful aquaculture planning. Due to the geographical setting of the Padang Pariaman Regency, aquaculture development is likely hindered by the vulnerable coastal area. Suitability assessment of aquaculture projects is crucial to specify the best method espousing sustainable development in the study area. This study aims to select the most proper location to be developed as a center of shrimp aquaculture in the Padang Pariaman Regency. This study employed the multi-criteria decision-making (MCDM), and analytical hierarchy process (AHP) approaches. This study combined the GIS-based analysis, AHP, and MCDM to yield the most proper location for aquaculture development. The three sub-models (engineering, water quality, and infrastructure) are overlaid using the weighted linear combination (WLC) technique. The infrastructure sub-model resulted in the highest coverage of highly suitable criteria with 61.74%. By contrast, the highest percentage of the unsuitable category was found in the water quality sub-model with 17.67%. Of particular concern, 87.5 % of the study area is suitable for aquaculture development. The remaining region is categorized as highly suitable with 11.93%, found in the eastern Padang Pariaman. Thus, we conclude that developing shrimp aquaculture in the study area is possible. Still, the future environmental impacts should be considered beforehand.